A Simple RP-HPLC Method Development and Validation for the Simultaneous Estimation of Naproxen and Rabeprazole - Mohammad Firoz Khan,Shaila Sharmin Zuthi,Md. Shahidulla Kayser,Md. Shariful Islam,Sharmeen Asad,Mohammad A. Rashid (Journal of Applied Pharmaceutical Science, 2016)
A simple, economic, selective, accurate, precise reverse phase high performance liquid chromatographic method for the simultaneous estimation of naproxen and rabeprazole sodium in pure and pharmaceutical dosage forms was developed and validated. Naproxen and rabeprazole sodium were well separated using a phenomenex ODS C18 column of dimension 4.6 mm × 250 mm, 10 µm and mobile phase comprised of sodium dihydrogen phosphate buffer (pH 7.5±0.1) and acetonitrile in the ratio of 70:30 (v/v) at the flow rate 1 mL/min and the detection was performed at 275nm. The retention time for naproxen and rabeprazole sodium were found to be 3.33 ± 0.027 and 7.61 ± 0.043 min, respectively. The developed method was validated for specificity, linearity, precision and accuracy according to ICH guidelines. The proposed method is highly specific and linear over the concentration range of 2.0-60.0 µg/mL and 1.0-30.2 µg/mL for naproxen and rabeprazole sodium, respectively. The intraday precision (% RSD) of naproxen and rabeprazole sodium was in the range of 0.39 - 1.88% and 0.20 -1.51% while the interday precision ranged from 0.08 - 1.34% and 0.73 -0.87%, respectively. The accuracy (in terms of recover) of the method varied from 99.4-104.2% and 98.1-100.6% for naproxen and rabeprazole sodium, respectively. The LOD and LOQ of naproxen and rabeprazole sodium were found to be 0.6 and 0.1 µg/mL and 1.7 and 0.4 µg/mL, respectively. The sample solutions were stable for at least three hours. However, the developed method was successfully applied to assay naproxen and rabeprazole sodium brands available in Bangladesh.
Keywords: Naproxen,Rabeprazole sodium,Retention time,Sample stability.